Interrelationships Between Ovarian Dynamics and Blood Plasma Profile in Double Ovsynch Treated Jaffrabadi Heifers and Buffaloes - Raval, Rupesh J.; Dhami, Arjun J.; Kavani, Fulabhai S.; Vijyeta, Hardeep P. (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
A study was carried out on post-pubertal acyclic Jaffrabadi buffalo heifers (n = 12, age 40-50 months) and >90 days postpartum lactating acyclic buffaloes (n = 6) employing double Ovsynch protocol to evaluate the treatment response, ovarian dynamics, and hormonal and biochemical profile assessed on different days of treatment till day 35 post-FTAI and their correlations. The protocol consisted of i/m injections of 20 µg Buserelin acetate, a GnRH analogue on day 0, 10, 17 and 26, and 500 µg PGF2α, Cloprostenol, on day 7 and 24, with a timed insemination on day 27. The populations of small (4 mm), medium (4-8 mm) and large (>8 mm) size follicles, and the diameters of largest/ dominant and subordinate follicles did not vary between double Ovsynch treated acyclic heifers and buffaloes, but they were significantly (p <0.05) interrelated among themselves in both the categories of animals. The overall mean plasma levels of LH, estrogen. insulin and conception rate were significantly (p <0.05) higher and plasma FSH and total cholesterol were lower in treated heifers than in buffaloes. However, the levels of plasma FSH, LH, estrogen, progesterone and insulin concentrations did not reveal any appreciable correlations among themselves and with most of the follicular traits in buffaloes, but in heifers plasma LH had significant correlations with diameter of subordinate follicles and plasma total protein. Plasma estrogen was significantly (p <0.01) correlated with blood glucose, protein and cholesterol in buffaloes, while progesterone showed significant negative correlations with blood glucose, total protein and most of the follicular traits in heifers. Plasma protein showed significant positive correlations with plasma insulin and cholesterol levels, and cholesterol with blood glucose, but their correlations with follicle population and diameter were negligible. It was concluded that higher conception rate in double Ovsynch treated acyclic heifers could be due to better synchrony of follicular events and plasma biochemical and endocrine constituents, culminating into ovulatory induced estrus compared to multiparous buffaloes.